2017
DOI: 10.1080/02640414.2017.1288296
|View full text |Cite
|
Sign up to set email alerts
|

Visual abilities distinguish pitchers from hitters in professional baseball

Abstract: This study aimed to evaluate the possibility that differences in sensorimotor abilities exist between hitters and pitchers in a large cohort of baseball players of varying levels of experience. Secondary data analysis was performed on 9 sensorimotor tasks comprising the Nike Sensory Station assessment battery. Bayesian hierarchical regression modelling was applied to test for differences between pitchers and hitters in data from 566 baseball players (112 high school, 85 college, 369 professional) collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…There is a growing body of literature on the existence of elevated levels of atypical handedness in conditions such as dyslexia (e.g., Vlachos, Andreou, Delliou, & Agapitou, 2013), schizophrenia (e.g., Tran & Voracek, 2015), autism spectrum disorder (ASD) (e.g., Markou, Ahtam, Papadatou-Pastou, 2017), deafness (e.g., Papadatou-Pastou & Sáfár, 2016), and intellectual disability (e.g., Papadatou-Pastou & Tomprou, 2015). Moreover, a link with left-(or mixed-) handedness has been investigated with mixed findings within a multitude of positive traits, such as mathematical and verbal talent (e.g., Bower, 1985), ability sports such as baseball (e.g., Klemish et al, 2017) and fencing (e.g., Voracek, Reimer, Ertl, & Dressler, 2006), as well as talent in art (e.g., Singg & Martin, 2016) and music (e.g., Kopiez, Galley, & Lee, 2006).…”
Section: Handedness and Cerebral Lateralizationmentioning
confidence: 99%
“…There is a growing body of literature on the existence of elevated levels of atypical handedness in conditions such as dyslexia (e.g., Vlachos, Andreou, Delliou, & Agapitou, 2013), schizophrenia (e.g., Tran & Voracek, 2015), autism spectrum disorder (ASD) (e.g., Markou, Ahtam, Papadatou-Pastou, 2017), deafness (e.g., Papadatou-Pastou & Sáfár, 2016), and intellectual disability (e.g., Papadatou-Pastou & Tomprou, 2015). Moreover, a link with left-(or mixed-) handedness has been investigated with mixed findings within a multitude of positive traits, such as mathematical and verbal talent (e.g., Bower, 1985), ability sports such as baseball (e.g., Klemish et al, 2017) and fencing (e.g., Voracek, Reimer, Ertl, & Dressler, 2006), as well as talent in art (e.g., Singg & Martin, 2016) and music (e.g., Kopiez, Galley, & Lee, 2006).…”
Section: Handedness and Cerebral Lateralizationmentioning
confidence: 99%
“…Additionally, athletes with better dynamic visual abilities, those that rely on acuity and contrast sensitivity judgments performed under temporal constraints, were shown to produce better 'plate discipline' batting statistics (e.g., O-Swing Propensity, which is discussed in the Methods section below; Laby et al, 2019). Furthermore, when compared between batters and pitchers with similar levels of experience, batters were shown to produce better performance on measures of visual acuity and depth perception than pitchers (Klemish et al, 2018), indicating that these skills are specific to the demand of hitting pitched ball, not throwing them. Lastly, eye tracking research suggested that batters shifting visual fixations more frequently between pitcher and home plate prior to batting showed better on-base percentage and batting average .…”
Section: Introductionmentioning
confidence: 97%
“…Given the exploratory nature of the study and the novelty of the sample, we did not have explicit hypotheses regarding the visual function of elite compared to intermediate level soccer players (see also Klemish et al, 2017). However, in accord with the general finding that athletes have better visual function than non-athletes (Gao et al, 2015;Hazel, 1995)…”
Section: Introductionmentioning
confidence: 98%
“…In reviewing the literature on visual function and training in sport, Hazel (1995) suggested that equivocal findings could be explained by the definitions used to determine group membership (for related issues of inter-participant variability, see Ward & Williams, 2003), as well as comparisons of various sports that have different visual requirements and a lack of consideration for the individual demands of player position. Indeed, while it is well accepted that the physical characteristics and demands placed on athletes such as soccer players differ as a function of playing position (e.g., Reilly, Bangsbo, & Franks, 2000), there has been limited consideration regarding visual function (for examples from other sports see Wimshurst, Sowden, & Cardinale, 2012;Klemish et al, 2017). This is surprising, particularly in invasion sports, where player position dictates a performer's tactical role and thus the types of behaviour required in a given situation.…”
Section: Introductionmentioning
confidence: 99%